Katuk Leaf Juice Improves Breast Milk Production in Postpartum Mothers: Evidence from an Indonesian Community Study - Kumalasari, Retno (Utan Kayu Publishing, 2025)
Low exclusive breastfeeding rates remain a pressing challenge in Indonesia, often linked to insufficient breast milk production. This study examined the effect of katuk leaf (Sauropus androgynus) juice—a traditional, non-pharmacological galactagogue—on breast milk output among postpartum mothers. Using a quasi-experimental, one-group pretest–posttest design, 20 mothers at Karangnunggal Community Health Center received fresh katuk juice twice daily for 14 days. Breast milk sufficiency was assessed objectively with a validated checklist and subjectively through maternal reports, classifying production as “sufficient” or “insufficient.” After the intervention, the proportion of mothers with sufficient milk increased from 30% to 85% (p = 0.001; large effect size r = 0.74). The positive effect is attributed to the phytochemical and nutritional content of katuk leaves, which may stimulate prolactin and oxytocin pathways. Findings support katuk juice as a safe, culturally relevant adjunct for lactation, and recommend its supervised use in maternal health programs to address breastfeeding barriers. ABSTRAK: Rendahnya angka pemberian ASI eksklusif tetap menjadi tantangan utama di Indonesia, yang sering kali terkait dengan produksi ASI yang tidak mencukupi. Penelitian ini bertujuan untuk mengkaji pengaruh jus daun katuk (Sauropus androgynus), salah satu galaktagog tradisional non-farmakologis, terhadap produksi ASI pada ibu postpartum. Melalui desain kuasi-eksperimen one-group pretest–posttest, sebanyak 20 ibu di Puskesmas Karangnunggal memperoleh jus daun katuk segar dua kali sehari selama 14 hari. Kecukupan ASI dinilai secara objektif menggunakan daftar periksa tervalidasi serta secara subjektif melalui laporan ibu, dengan klasifikasi produksi sebagai “cukup” atau “tidak cukup”. Setelah intervensi, proporsi ibu dengan produksi ASI cukup meningkat dari 30% menjadi 85% (p = 0,001; effect size besar r = 0,74). Efek positif ini dikaitkan dengan kandungan fitokimia dan nutrisi daun katuk yang dapat menstimulasi jalur prolaktin dan oksitosin. Temuan ini mendukung jus daun katuk sebagai intervensi pendamping yang aman dan relevan secara budaya untuk mendukung laktasi, serta merekomendasikan penggunaannya secara terpantau dalam program kesehatan ibu guna mengatasi hambatan menyusui.